The Impact of Bank Behavior, Financial Literacy on Investment Decisions, Mediation of Financial Inclusion and Debt Behavior. Study on Working Capital and Investment Debtors at Regional Development Bank Yogyakarta Indonesia - Kristanto HC, R. Heru (Technium Social Sciences Journal, 2021)
Bank behavior, financial literacy, financial inclusion, debt behavior, and investment affect the economic growth of an industry. The purpose of this research is to examine the effect of bank behavior, financial literacy, financial inclusion, debt behavior on investment decisions of working capital and investment debtors in the Regional Development Bank of Yogyakarta. Indonesia. Examine the mediating role of financial inclusion, debt behavior on investment decisions. The research sample are 280 debtors. The analysis model used mediation regression with the PLS program. The results showed that: Bank behavior has an effect on financial inclusion. Bank behavior has an effect on debt behavior. Financial literacy has an effect on financial inclusion. Financial literacy has an effect on debt behavior. Financial inclusion mediates the effect of bank behavior on investment decisions. Debt behavior mediates the effect of financial literacy on investment decisions. The managerial implication of this research is: the flexibility of providing credit to customers, must be followed by control of the use of funds. Financial literacy, financial inclusion and higher debtor debt behavior will increase the movement of the industry. The right investment will improve entrepreneurial and banking performance.